MAKING OF CONTINUOUS GASIFIER SYSTEM PROTOTYPE USING CORN COB AS FUEL - PRAMUDA SIRODZ (NIM : 23107014); Dosen Pembimbing : Dr. Ir. Willy Adriansyah, M
Corn cob is one of the potential alternative energy that can be used as a substitute for fosil fuel. Corn cob is very abundant in IndonesiaÃ‚Â’s agriculture. The utilization of biomass as a fuel, in this case is corn cob, gave two important advantages for the environment. First, the recycling of the carbon dioxide (CO2), therefore the CO2 emission to the atmosphere is equal to zero, and to solving the agriculture waste problem. However in the application, an appropriate technology is needed therefore the biomass can be used as a fuel energy, this technology was called gasification. The most fundamental background of this research is the needs of alternative fuel such as biomass in small home industry to replace fosil fuel, which is it price is increasing every year. In this research, gasifier protoype was designed by simulation method using computer softwares, Cycle-tempo and Computational Fluid Dynamics (CFD). The design then were precisionengineered and tested. The concept of this gasifier is consist of feeding, reactor, and burner sections. Corn cob was feeded into the reactor by screw conveyor. The gasification process take place inside the reactor and the gas flowed into the burner to be burnt. First trial showed that several modifications were needed so the gasifier could operate properly. From Cycle-tempo program, gas composition of the gasification process (syngas) were obtained. The simulation result showed that for reactor with diameter about 20.32 cm, the maximum reactor power is 19.38 kW. The syngas then burned in the burner and it needs to be burned completely. Simulation with CFD software showed the geometry of the burner is 6 inches in diameter and 50 cm in length. This research contains of several trials, and showed that the corn cob have to be pre-chopped into 5 mm x 5 mm before feeds into the reactor. Gasification process were done properly with corn cob mass flow about 6.48 kg/hour and oxidant mass flow about 10.8 kg/hour. Whitecolored fires were resulted from the syngas burning process and the gasification process were run continously. In this process, ashes were produce as waste and accumulated in a special part, a waste part with watershield. Light properties of the ashes caused it to floated in the watershield so the ashes could not leave the ashes waste part.